CCL2 (C-C Motif Chemokine Ligand 2) Biomarker Responses in Central Versus Peripheral Compartments After Focal Cerebral Ischemia. Issue 11 (30th September 2021) - Shi, Jingfei; Li, Wenlu; Zhang, Fang; Park, Ji Hyun; An, Hong; Guo, Shuzhen; Duan, Yunxia; Wu, Di; Hayakawa, Kazuhide; Lo, Eng H.; Ji, Xunming
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Inflammatory mediators in blood have been proposed as potential biomarkers in stroke. However, a direct relationship between these circulating factors and brain-specific ischemic injury remains to be fully defined. Methods: An unbiased screen in a nonhuman primate model of stroke was used to find out the most responsive circulating biomarker flowing ischemic stroke. Then this phenomenon was checked in human beings and mice. Finally, we observed the temporospatial responsive characteristics of this biomarker after ischemic brain injury in mice to evaluate the direct relationship between this circulating factor and central nervous system–specific ischemic injury. Results: In a nonhuman primate model, an unbiased screen revealed CCL2 (C-C motif chemokine ligand 2) as a major response factor in plasma after stroke. In mouse models of focal cerebral ischemia, plasma levels of CCL2 showed a transient response, that is, rapidly elevated by 2 to 3 hours postischemia but then renormalized back to baseline levels by 24 hours. However, a different CCL2 temporal profile was observed in whole brain homogenate, cerebrospinal fluid, and isolated brain microvessels, with a progressive increase over 24 hours, demonstrating a mismatch between brain versus plasma responses. In contrast to the lack of correlation with central nervous system responses, 2 peripheral compartments showed transient profiles that matched circulating plasma signatures. CCL2 protein in lymph nodes and adipose tissue was significantly increased at 2 hours and renormalized by 24 hours. Conclusions: These findings may provide a cautionary tale for biomarker pursuits in plasma. Besides a direct central nervous system response, peripheral organs may also contribute to blood signatures in complex and indirect ways.